Analysing Life Cycle Stages of Indian Meal Moth, Plodia interpunctella (Hübner) on Four Different Diets - Onaolapo, Akinneye Joseph; Kemisola, Olufemi-salami Folasade; Samson, Salami, Olufemi (International Journal of Scientific Research and Management (IJSRM), 2017)
The life cycle stages of Indian meal moth, Plodia interpunctella (H) was studied on four different diets:whole maize flour, whole wheat flour, breadfruit flour and a formulated diet, under ambient laboratoryconditions of 28±2oC and 75±5% R.H. The proximate composition of the diets, oviposition, larva instarstages, and the complete developmental duration from egg to adult of the moth were examined on the fourdifferent diets. The result showed that the percentage protein value of the formulated diet was significantlyhigher (14.58) than other diets. The oviposition of the moth on the diets ranges between 1-3 days andabout 70% of the eggs laid were on the first day of oviposition in all the diets. The highest number of eggslaid was observed on moths reared on maize flour. Incubation of eggs examined on the diets ranges from3-4 days. Also, there were variations in the number of larva instar stages in the four diets. The formulateddiet recorded the lowest period of pupation (6.33 days) and the total developmental average period(23.50days). The study clearly showed that the formulated diet is suitable for rearing P. interpunctellaunder laboratory conditions.